Internalization of Spiritual Values in Forming Student Character Through Tahfidzul Qur’an Extracurricular Activities - Akublan Siregar; Yusnaili Budianti; Muhammad Rifai (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to discover the existence of spiritual values ​​in extracurricular activities, the process of inculcating spiritual values ​​in shaping students’ character, and the obstacles and results of applying spiritual values ​​in extracurricular activities of Tahfizul Qur'an at Pondok Pesantren Al-Mukhtariyah Sungai Dua. This study uses qualitative research with a descriptive approach. In collecting data, researchers used the methods of observation, interviews, and documentation. The results showed that Tahfizul Qur'an extracurricular activities were carried out before entering class, with Murajaah and repetition of memorizing. The process of inculcating spiritual values ​​is carried out by refraction, combined learning methods, learning strategies emphasizing the role of mentor teachers, daily evaluations by checking memorization, monthly evaluations with verse connecting verse games, and semester evaluations with the Tahfiz exam. The obstacles in instilling spiritual values ​​are students' awareness, including taking advantage of the extended learning time in Islamic boarding schools, then the lack of cooperation with parents about memorizing children to what extent the child's abilities.